Money Laundering and Corruption - Reda Manthovani (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Crime is a term that contains a basic understanding in the science of law, as a term formed with awareness in giving certain characteristics to criminal law events. Money laundering or money laundering as a crime has been the focus of attention since the 1980s, especially in the context of crime of drug trafficking (psychotropics and narcotics). The problem of money laundering was only declared a crime by Law Number 15 of 2002 concerning the Crime of Money Laundering which was legalized and promulgated on April 17 2002. Law Number 15 of 2002 Article 2 concerning Money Laundering is an act that aims to hide or disguise the origin of money or assets obtained from the proceeds of crime which are then converted into assets that appear to originate from legitimate activities. Understanding the Money Laundering, Financial Action Task. The Force on Maney Laundering (FATF) formulates that money laundering is the process of concealing or disguising the origins of proceeds of crime. The development of corruption in Indonesia is in a dangerous stage. If we compare corruption in Indonesia to a disease, corruption in Indonesia develops in three stages which are elastic, endemic and systematic. In addition to its transnational crimes, corruption is also referred to as an extraordinary crime. Corruption in Indonesia has spread throughout the government and all layers of society so that efforts to eradicate corruption are still faltering, especially with resistance by parties whose interests are disturbed by the agenda of eradicating corruption. Corruption and money laundering have a very close relationship. This can be clearly seen in Article 2 paragraph 1 of Law Number 8 of 2010 concerning the Prevention and Eradication of Money Launderin.